Predicted Functional Implications of Phosphorylation of Regulator of G Protein Signaling Protein in Plants - Tunc-Ozdemir, Meral; Li, Bo; Jaiswal, Dinesh K.; Urano, Daisuke; Jones, Alan M.; Torres, Matthew P. (Frontiers in Plant Science, 2017)
Heterotrimeric G proteins function in development, biotic, and abiotic stress responses, hormone signaling as well as sugar sensing. We previously proposed that discrimination of these various external signals in the G protein pathway is accomplished in plants by membrane-localized receptor-like kinases (RLKs) rather than G protein coupled receptors. Arabidopsis thaliana Regulator of G Signaling protein 1 (AtRGS1) modulates G protein activation and is phosphorylated by several RLKs and by WITH-NO-LYSINE kinases (WNKs). Here, a combination of in vitro kinase assays, mass spectrometry, and computational bioinformatics identified and functionally prioritized phosphorylation sites in AtRGS1. Phosphosites for two more RLKs (BRL3 and PEPR1) were identified and added to the AtRGS1 phosphorylation profile. Bioinformatics analyses revealed that RLKs and WNK kinases phosphorylate plant RGS proteins within regions that are conserved across eukaryotes and at a high frequency. Four phospho-sites among 14 identified are proximal to equivalent mammalian phosphosites that impact RGS function, including: pS437 and pT267 in GmRGS2, and pS339 and pS436 in AtRGS1. Based on these analyses, we propose that pS437 and pS436 regulate GmRGS2 and AtRGS1 protein interactions and/or localization, whereas pT267 is important for modulation of GmRGS2 GAP activity and localization. Moreover, pS339 most likely affects AtRGS1 activation.